Resistir à censura da Inquisição - Olival, Fernanda (2023)
This chapter analyses an inquisitorial process motivated by the sale of a pamphlet that had not been censored before it was printed. It also analyses the consequences for the printer who dared to challenge the Inquisition's power over the written word. The aim is to explain the importance of freedom of expression.